The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1007/s00431-016-2690-1
|View full text |Cite
|
Sign up to set email alerts
|

Post-test probability for neonatal hyperbilirubinemia based on umbilical cord blood bilirubin, direct antiglobulin test, and ABO compatibility results

Abstract: • The diagnostic value of the triad umbilical cord blood bilirubin measurement, direct antiglobulin testing and blood group analysis for neonatal hyperbilirubinemia remains unclear in literature. • Currently no guideline recommends screening for hyperbilirubinemia using umbilical cord blood. What is New: • Post-test probability for hyperbilirubinemia correlated exponentially with umbilical cord blood bilirubin in different risk groups defined by direct antiglobulin test and ABO blood group compatibility result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
0
8
1
1
Order By: Relevance
“…However, our finding is higher than that found in a previous meta-analysis (21). In contrast, the prevalence of hyperbilirubinemia found in our study was substantially lower than that found in previous systematic reviews carried out in Pakistan (22), Myanmar (23) and global burden diseases GBD (24,25). These differences might be the result of different diagnostic standards for neonatal hyperbilirubinemia, early diagnosis and treatment in developed countries, and the early discharge of healthy late-preterm and full-term newborns.…”
Section: Discussioncontrasting
confidence: 96%
“…However, our finding is higher than that found in a previous meta-analysis (21). In contrast, the prevalence of hyperbilirubinemia found in our study was substantially lower than that found in previous systematic reviews carried out in Pakistan (22), Myanmar (23) and global burden diseases GBD (24,25). These differences might be the result of different diagnostic standards for neonatal hyperbilirubinemia, early diagnosis and treatment in developed countries, and the early discharge of healthy late-preterm and full-term newborns.…”
Section: Discussioncontrasting
confidence: 96%
“…CBBs are easily obtained from umbilical cord blood and have a short turnaround time. In a retrospective study of 12,993 Belgian neonates, a CBB of 1.98 mg/dL had a sensitivity at 71% with a specificity of 77% for a TSB concentration >95 th percentile [ 13 ]. In our study, a slightly lower CBB cut-off value of 1.85 mg/dL had a greater sensitivity at 79% and lower specificity at 72%.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, a slightly lower CBB cut-off value of 1.85 mg/dL had a greater sensitivity at 79% and lower specificity at 72%. The negative predictive values (98–99%) and AUCs (0.81–0.82) were similar, and both studies had low positive predictive values [ 13 ]. In subgroup analysis of subjects with a positive DAT in this study, the sensitivity and specificity improved to 92% and 70%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If there were no previous TSB measurements, ROR was calculated by using an estimated TSB at birth of 1.7 mg/dL. 16,17 Inpatient feeding was categorized as exclusive breast milk feeding, mixed breast milk and formula feeding, or exclusive formula feeding on the basis of nursing flowsheets documenting feeding. For comparison, we developed a model based on the Bhutani Nomogram by assigning each predischarge TSB a Bhutani risk zone (high, high-intermediate, low intermediate, or low).…”
Section: Predictors and Modelsmentioning
confidence: 99%